A Psychometric Theory that Measures up to Marketing Reality: An Adapted Many Faceted IRT Model. Issue 2 (May 2014) - Wang, Luming; Finn, Adam
The marketplace has been defined by the interaction between consumers and brands, which has been recognized by the majority of marketing literatures with the exception of the measurement literature. Measurement researchers in marketing have been continuously working on improving the quality of measurement of marketing constructs by applying psychometric theories from the early Classical Test Theory to later generations such as Generalizability Theory and Item Response Theory. But only main effects (normally consumers, sometimes brands) have been focused on, and interactions between them are either ignored or treated as measurement error. This is surprising, given the voluminous literature in other areas of marketing (e.g., marketing segmentation, customer lifetime value, and customer relationship management) that build their entire frameworks on the interpretation and usage of this interaction. In the current research, we propose a new Many Faceted Item Response Theory model to fill this gap in measurement literature. Two sets of indexes describe consumers (and brands); individual main effects (and brand main effects) and brand-specific individual effects (or individual-specific brand effects). Soft drink brand equity data were used for the empirical examination.